CATEGORY II EVALUATION OF AN F-111A AIRCRAFT IN THE CLIMATIC LABORATORY AND TROPICAL, ARCTIC, AND DESERT ENVIRONMENTS VOLUME I. TEST RESULTS. - Coombs, Charles P.; Spaulding, Robert L. (1968)
The Category II climatic tests of a pre-Super Weight Improvement Program (pre-SWIP) F-111A aircraft were conducted in four phases which consisted of static testing in the Climatic Laboratory, Eglin Air Force Base, Florida, and both ground and flight testing in tropical, arctic, and desert environments. The objectives of these tests were to determine the adequacy of the aircraft and the subsystems for operation in extreme environments, define deficiencies uncovered, determine special operating procedures, make recommendations for corrective actions, and compile environmental data for future use. This report is a compilation of all the test results which were previously submitted to the F-111 System Program Office (SPO) as four individual Flight Test Reports each covering a single phase of testing. Volume I describes the test procedures, presents selected graphical data, discusses test results, analyzes uncovered deficiencies, presents conclusions, makes recommendations for correction, and lists SPO comments/action on the recommendations. It also contains appendixes which summarize Unsatisfactory Reports and Quality Assurance Data Reports submitted from the various test sites and lists the instrumentation parameters which were recorded. (Author)